Facile Synthesis of NaYF4:Yb, Tm@TiO2 Core‐Shell Structured Composite with Enhanced Photocatalytic Activity for Degradation of RhB Dye. Issue 38 (18th October 2019) - Pan, Yusong; Feng, Pengpeng; Yin, Minyuan; Fang, Hongjun; Pan, Chengling
Abstract: It is an effective method to explore the full spectrum responsive photocatalysts for enhancing their photocatalytic activity. Herein, we have combined the upconversion phosphor with semiconductor to design the full‐spectrum light responsive photocatalyst. A facile approach has been developed for synthesis of NaYF4 :Yb, Tm@TiO2 core‐shell structured composite. The morphologies, crystal phases, chemical compositions, optical performance, and photoelectric properties were characterized. Based on SEM and TEM observation, the formation mechanism of NaYF4 :Yb, Tm@TiO2 composite was discussed in detail. The results of photodegradation experiment showed that 22% of Rhodamine B dye in the solution was photodegradated by NaYF4 :Yb, Tm@TiO2 composite under NIR light irradiation within 150 min, suggesting that the NaYF4 :Yb, Tm@TiO2 core‐shell structured composite displayed photocatalytic activity under NIR light irradiation. Furthermore, the photocatalytic ability of NaYF4 :Yb, Tm@TiO2 is obvious superior to that of TiO2 under the full‐spectrum light irradiation. Abstract : NaYF4 :Yb, Tm@TiO2 Core‐shell structured composite was synthesized to investigate its photocatalytic activity for degradation of RhB dye under full‐spectrum light irradiation. NaYF4 :Yb, Tm@TiO2 composite exhibited superior photocatalytic activity which could be attributed to the efficient trasformation NIR light to UV and visible light by NaYF4 :Yb, Tm core.